Ionic conduction in Li3Na(NH2)4: Study of the material design for the enhancement of ion conductivity in double-cation complex hydrides - Biswajit Paik; Hiroyuki Oguchi; Toyoto Sato; Shigeyuki Takagi; Arunkumar Dorai; Naoaki Kuwata; Junichi Kawamura; Shin-ichi Orimo (AIP Advances, 2019)
Complex hydrides have collected recent attention as a new class of solid electrolytes with potential applications in all-solid-state batteries. To improve ionic conduction in the complex hydrides, multi-cation crystal structure can be attractive. It will allow tuning the cation dynamics via structure modification depending on types and number of additional cations. However, multi-cation crystal structure struggles with the inter-cation scattering among different cations. To address this issue, understanding the conduction mechanisms in the multi-cationic crystals is indispensable. Here, we study cationic conduction in a double-cation (Li and Na) complex hydride Li3Na(NH2)4, which is formed by replacing Li (with Na) from specific lattice site of LiNH2 without altering the crystal symmetry. The nuclear magnetic resonance (NMR) measurements found that Li3Na(NH2)4 is a Li-ion conductor with negligibly small Na-ion conduction. This finding is critically important to elucidate Li-ion conduction mechanism in Li3Na(NH2)4. Enhanced Li-ion conduction in Li3Na(NH2)4 is achieved by (a) suppressing diffusion of Na cation trapped at the strategically located 2c lattice sites under deep potential well; and (b) by increasing the Li defect concentration influenced by the larger volume of the Li metastable sites due to Na substitution into LiNH2. Our study will provide the design principle for multi-cation complex hydrides, and accelerate development of superior solid electrolytes for all-solid-state batteries.